PENGARUH CORPORATE GOVERNANCE TERHADAP CASH FLOW RETURN ON ASSETS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019- 2021 - Alcianno G. Gani (JURNAL MITRA MANAJEMEN, 2023)
The research aims to determine the effect of the implementation of Good Corporate Governance (Institutional Ownership, Audit Committee, Proportion of Total Members of the Board of Commissioners, and Number of Members of the Board of Directors) on the Company's Financial Performance. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Corporate governance as an independent variable is proxied by Institutional Share Ownership, Existence of an Audit Committee, Independent Board of Commissioners, and Number of Directors. The company's financial performance as the dependent variable is proxied by CFROA. The data source is from the website www.idx.co.id in the form of financial reports and annual reports with a population of 393 financial reports (131 companies) using purposive sampling, 136 samples of financial reports were obtained. From processing using SPSS 25, the results obtained were Institutional Ownership 0.456, Audit Committee 0.046, Board of Commissioners Proportion 0.132, and Number of Directors 0.000, so it can be concluded that Institutional Ownership and Proportion of Number of Board of Commissioners have no effect on Company Performance, while the Audit Committee and Number of Directors have an effect on Company performance. If the test is carried out simultaneously, the result is 0.000 (so that together Institutional Ownership, Existence of an Audit Committee, Proportion of Total Members of the Board of Commissioners, and Number of Directors have a significant positive effect on Company Performance. The test results for the coefficient of determination show the numbers 24.1%, 75 .9% is influenced by other variables not examined in this study. Keywords: Good Corporate Governance (GCG), Financial Performance.